Dinamika Audit Judgment: Moderasi Kompleksitas Tugas dalam Hubungan Time Budget Pressure, Framing, dan Kecerdasan Emosional - Ihsanuddin, Mokhammad; Abbas, Dirvi Surya; Mikrad (Universitas Swadaya Gunung Jati, 2026)
This study is important as the quality of audit judgment is often influenced by psychological and situational factors that may undermine auditors’ objectivity and professionalism, as evidenced by several sanctions imposed on Indonesian Public Accounting Firms. The purpose of this research is to analyze the effect of time budget pressure, framing, and emotional intelligence on audit judgment, and to examine the moderating role of task complexity. This study employed a quantitative approach with a survey method, collecting responses from 170 auditors across 25 firms in Tangerang Raya. Data were obtained through Likert-scale questionnaires and analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with SmartPLS 4.0. The results indicate that time budget pressure, framing, and emotional intelligence significantly influence audit judgment. Moreover, task complexity was found to purely moderate the relationships among these variables. The findings conclude that managing time pressure, ensuring objective information framing, and enhancing auditors’ emotional intelligence are crucial in improving audit decision quality. The practical implication suggests that audit firms should develop training programs and managerial strategies to strengthen auditors’ resilience against work pressure and task complexity, thereby maintaining public trust in the auditing profession.